Adsorption of heavy metals in waste water using biological materials - Candelaria Tejada-Tovar; Ángel Villabona-Ortiz; Luz Garcés-Jaraba (TecnoLógicas, 2015)
Biosorption is a process that allows active or passive uptake of metal ions due to the property that different living or dead biomass have to bind and accumulate these pollutants by different mechanisms. The application of low-cost materials obtained from different biomass from microbial flora, agro-industrial waste and algae has been investigated to replace the use of conventional methods for the removal of contaminants such as heavy metals. Some of the metals of greatest impact to the environment due to its high toxicity and difficult to remove are chromium, nickel, cadmium, lead, and mercury. In this paper, an overview of adsorption as an alternative process for the removal of contaminants in solution and biomass commonly used in these processes, as well as some of the modifications made to improve the efficiency of adsorption of these materials is presented. It was concluded that the use of adsorption in the removal of pollutants in aqueous solution using waste biomass is applicable to these decontamination processes avoiding subsequent problems such as the generation of chemical sludge, and generating an alternative to use materials considered as waste. It is further identified that such factors as the pH of the solution, particle size, temperature, and concentration of metal effect on the process.